Outcome-Based Education Standards and Practices in Augustinian Schools in Negros - Melona Q. Guitche; Araceli C. Doromal (Philippine Social Science Journal, 2020)
This study assessed the extent of implementation of OBE Standards and Practices in the Association of Schools of the Augustinian Sisters (ASAS) in Negros as assessed by students, teachers, and academic administrators using the survey questionnaire. The descriptive-comparative and correlational design were employed. Mean, ANOVA with Scheffe as Post-Hoc Test, and Pearson r were used to analyze the data collected. As a whole, the findings indicated a generally high extent of implementation of the standards. Students and teachers gauged it as high, while academic administrators as very high. The OBE Practices were very high. A significant difference in the implementation of OBE Standards and Practices and significant relationship were noted. A conceptual model of quality assurance framework for continuous improvement programs on curriculum development was designed. The results signify that outcomes have been established, and the curriculum was designed to address the knowledge, skills, and attitude they need to demonstrate the established outcomes.